2014
DOI: 10.7182/pit2014248
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Medical Students and Staff toward Organ Donation in Cases of Brain Death: A Survey at Shiraz University of Medical Sciences

Abstract: Most participants (78%) had favorable attitudes toward donating their own organs after brain death. However, only about 25% of them carried an organ donation card. In addition to public media, the main sources of information about organ donation after brain death were their professors and textbooks. An association in charge of improving public awareness and facilitating the process of registration and issuance of donation cards appears to be necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 16 publications
0
9
1
Order By: Relevance
“…Eight studies have analyzed the knowledge of the BD concept among students. There are studies in Iran, 9,10 Brazil, 3,11 United States, 7 Polonia, 12 and Japan, 13,14 and in all geographical areas, the studies show worse results than described in our series. In general, the authors have demonstrated a low level of knowledge and inadequate understanding of the criteria of BD.…”
Section: Discussioncontrasting
confidence: 76%
“…Eight studies have analyzed the knowledge of the BD concept among students. There are studies in Iran, 9,10 Brazil, 3,11 United States, 7 Polonia, 12 and Japan, 13,14 and in all geographical areas, the studies show worse results than described in our series. In general, the authors have demonstrated a low level of knowledge and inadequate understanding of the criteria of BD.…”
Section: Discussioncontrasting
confidence: 76%
“…16 Organ donation after brain death has high potential in many developing countries where consensus among the public and health care providers may be particularly high. For example, in Iran, 78% of medical staff and students had favorable attitudes to donation after brain death, 17 and 91% of health care professionals in Karachi, Pakistan, identified brain death correctly. 18 In Uruguay, donation after brain death is increasing, while in the United Kingdom, it remains stable.…”
Section: /22 [59%] Upper-middle Income; 22/36 [61%]mentioning
confidence: 99%
“…The findings of several studies indicate that there is a need to educate members of HCT especially the nurses about organ donation, for better preparation of the families of brain dead patients. [5][6][7][8] Lot of patience is required on the part of nurses, as one sitting may not be sufficient to prepare the family of the brain dead patients. Given an excessive load of patients and the inability to spare the nurses from the ICU for in-service education, CBSIM can be an effective way of imparting knowledge in any health care facility.…”
Section: Discussionmentioning
confidence: 99%
“…However, appropriate training is lacking among HCP especially nurses. [5][6][7][8][9] This can be attributed to inadequate information provided at pre-service nursing education programs and the diversity in training of nurses across the country.…”
Section: Introductionmentioning
confidence: 99%